OTIVATION AND COGNITIVE PROCESSES: PUBLISHING OBJECTS OF THE DIALECTIC JOURNAL (2020 - 2025) - Jackson Arley Acevedo Clavijo,; Jennifer Yurley Soto Ruiz, (LÍNEA IMAGINARIA, 2025)
The purpose of this research article is to conduct a bibliometric analysis of the journal Dialéctica published by the Universidad Pedagógica Experimental Libertador (UPEL), based on the phenomena studied within the framework of educational practice, such as Motivation and Cognitive Processes, examining and describing the details of the journal's scientific output in this specific field. This analysis is based on aspects such as thematic trends and the corresponding impact of this academic output on the consolidation of research processes as a core activity of postgraduate academic training at this institution. The cited studies demonstrate the significant contributions made by researchers and the journal to the dissemination and social appropriation of scientific knowledge regarding the influence of these mental factors on the consolidation of meaningful experiences in educational practice.